2000
DOI: 10.1007/bf03018945
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, dose-response, and adverse effects of droperidol for prevention of postoperative nausea and vomiting

Abstract: Purpose: To estimate the efficacy and harm produced by droperidol in the prevention of postoperative nausea and vomiting (PONV). Methods: Systematic search (MEDLINE, EMBASE, Cochrane library, hand-searching, bibliographies, all languages, up to May 1999) for randomised comparisons of droperidol with placebo in surgical patients. Relevant end points were prevention of early PONV (up to six hours postoperatively), and late PONV (24 hr), and adverse effects. Combined data were analysed using relative risk and NNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
1
19

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(115 citation statements)
references
References 101 publications
(52 reference statements)
1
93
1
19
Order By: Relevance
“…For both early and late vomiting, the best efficacy was with 1.5 to 2.5 mg (NNT = 7). 31 In children, the recommended dose is 50 to 75 µg·kg -1 with a NNT of 4 (IIA). 31 It has a long duration of action (as long as 24 hr following administration) probably due to its strong binding affinity to the emetic receptors; even though its half-life is relatively short (three hours).…”
Section: Older Generation Antiemeticsmentioning
confidence: 99%
See 2 more Smart Citations
“…For both early and late vomiting, the best efficacy was with 1.5 to 2.5 mg (NNT = 7). 31 In children, the recommended dose is 50 to 75 µg·kg -1 with a NNT of 4 (IIA). 31 It has a long duration of action (as long as 24 hr following administration) probably due to its strong binding affinity to the emetic receptors; even though its half-life is relatively short (three hours).…”
Section: Older Generation Antiemeticsmentioning
confidence: 99%
“…31 In children, the recommended dose is 50 to 75 µg·kg -1 with a NNT of 4 (IIA). 31 It has a long duration of action (as long as 24 hr following administration) probably due to its strong binding affinity to the emetic receptors; even though its half-life is relatively short (three hours). 60 Droperidol is most effective when given at the end of surgery (IIA).…”
Section: Older Generation Antiemeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systemic review suggested that droperidol's antiemetic efficacy, when given at the end of surgery, may have been exaggerated. 2 Since haloperidol is pharmacologically similar to droperidol for the control of nausea and vomiting, and since the time to peak plasma concentration from intravenous injection is only five to 15 min, 17 the drug might be more effective when administered at the end of surgery, thereby producing a more sustained antiemetic effect in the postoperative period. However, our results show that haloperidol 2 mg iv administered during induction of anesthesia, achieves similar antiemetic efficacy as compared to the same drug dose given 30 min prior to completion of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1 Droperidol, a butyrophenone, has frequently been used for preventing PONV after general anesthesia. 2 However, recent warnings regarding the safety of droperidol have limited its routine use. 3 Haloperidol is also a butyrophenone with antiemetic properties, but without the U.S. Food and Drug Administration (FDA) restrictions.…”
Section: Conclusion : Le Moment Choisi Pour L'administration De 2 Mg mentioning
confidence: 99%